Circular ring shaped ultra-wideband metamaterial absorber with polarization insensitivity for energy harvesting - John Bosco John Paul; Aruldas Shobha Rekh (Institute of Advanced Engineering and Science, 2022)
A circular ring-shaped metamaterial (CRM) absorber was designed to harvest radio frequency (RF) energy in the ultra-wideband (UWB) frequency band applications. The proposed metamaterial unit cell features a circular shaped structure, with rectangular strip lines connected in the form of a cross leaving a square shaped slot at center. The unit cell dimensions are 15×15×1.6 mm. The absorber was etched on a low cost FR4 substrate having a dielectric constant of 4.4. Ansys high frequency structure simulator (HFSS) software was used for simulation and the analysis were carried out for unit cell, 2×2, 3×3, and 4×4 array structures. The absorber parameters plotted are absorption characteristics and reflection characteristics. Also, the metamaterial parameters (μeff) and (εeff) are also retrieved from the absorber parameters and analyzed. From the analysis, the values (μeff) and (εeff) were found to be negative, leaving refractive index also negative (n<0), which proved the metamaterial property. The proposed CRM absorber showed good absorption characteristics of more than 80% and also metamaterial property in the entire UWB band (4-13 GHz). Hence the absorber proves to be a good candidate in powering low power sensors/microcontrollers for internet of things (IoT) applications.